Tren Dakwah Nawaning di Era New Media - Fabriar, Silvia Riskha; Muhajarah, Kurnia (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
Sophistication in technology and media allows Islamic boarding school people to reach a wider audience, engage in religious discussions, and build networks with communities that have similar interests. The affects the daily activities of Islamic boarding school women, especially Nawaning, including da’wah. Nawaning is starting to exist in various places and in digital media. Previously, da’wah carried out around Islamic boarding schools, but now it can be heard by a large audience through new media. The article aims to explore the trend of Nawaning da'wah in the new media era. This study is qualitative research with a media ecology approach. Primary data obtained from several nawanings in Central Java and parts of Nawaning Nusantara or JPPPM. Secondary data from Nawaning’s social media accounts and related online and offline documents. Data collected by interviews and documentation. The results of this article show that the trend of da’wah among Ning in the new media era is preaching using social media. They deliver a variety of material, with da'wah methods according to the tendencies of each nawaning and with an approach tailored to the purpose of the da’wah. The reformulation of Nawaning da'wah through new media is a significant step in efforts to carry out da'wah that is more relevant, inclusive, and effective in an increasingly connected and rapidly changing environment.